The temporal dimension in climate adaptation and mitigation strategies and solutions aimed to increase urban integrated resilience - Clemente, Maria Fabrizia; Puzone, Sabrina (Contesti. Città, territori, progetti, 2026)
Climate change poses critical challenges to urban and metropolitan settlements, increasing their vulnerability to extreme events due to unsustainable and resilient development patterns. This article proposes a conceptual framework that integrates climate-proof strategies and actions into the four phases of disaster risk management (DRM): preparedness, absorption, response/recovery and long-term adaptation. Emphasizing the temporal dimension of resilience, the study highlights the need for dynamic, multi-scalar and systemic design approaches that enhance urban capacity to anticipate, withstand and recover from climate-related impacts. The framework aims to support decision-making processes by aligning architectural and urban design interventions with specific DRM phases, providing a basis for conscious, resilient and sustainable design of urban settlements.